LITERATUR REVIEW: FAKTOR-FAKTOR RISIKO YANG BERKONTRIBUSI TERHADAP KEKERASAN DALAM PACARAN PADA REMAJA DI INDONESIA - Lestyoningsih, Ika Harni (Universitas Negeri Malang, 2024)
In Indonesia, the first order of violence in the personal realm is cases of dating violence which were reported to the National Commission on Violence Against Women in 2023, totaling 3,528 cases, followed by 3,205 cases of violence against wives and then 725 cases of violence against girls. There was an increase in cases from the previous year. This situation is related to factors such as access to information, environment, socio-economics and family upbringing. The impact of dating violence causes long-term problems for victims related to physical, mental and psychological trauma, repeated cycles of violence, socio-economic, behavioral changes and decreased quality of life. Handling violence in dating requires a holistic approach involving various elements in society, victims, perpetrators, legal institutions, community support services, especially related to promotive activities in increasing youth knowledge. This research method uses a literature review, articles are collected using search engines such as Google Scholar. The criteria for articles used are those published in 2014-2024. Based on the results of the situation analysis, risk factors contribute to dating violence among teenagers in Indonesia.The aim of this research is to find out more deeply about the risk factors that contribute to dating violence among teenagers in Indonesia. The conclusion is that by knowing the risk factors for violence, society can take proactive steps to reduce incidents of dating violence.